Analisis Laporan Keuangan KSPPS Nur Insani Tahun 2021-2023 dengan Rasio Keuangan - Ammara Ghina Abiyyu Zahira; Anisah Rusnadi; Muhammad Zaqi Subagya; Feby Dwi Lestari; Titania Zahra Nurliyan (Universitas 45 Surabaya, 2026)
This study aims to evaluate the financial performance of KSPPS Nur Insani for the 2021–2023 period through the analysis of various financial ratios, such as liquidity, solvency, profitability, and activity. The method used is descriptive quantitative, utilizing secondary data obtained from the cooperative's financial statements. The analysis results indicate that the cooperative has a very high level of liquidity, indicating a fairly good ability to meet short-term obligations. However, the cooperative's capital structure is still dominated by debt, indicating a dependence on external financing. The cooperative's profitability shows a positive trend, with profits continuing to increase annually. The activity ratio also shows stable performance despite a decline in fixed asset utilization, which could be an area of ​​concern for further management. Overall, the financial condition of KSPPS Nur Insani is in the good category and has shown positive developments over the past three years. The cooperative can maintain this performance by increasing the efficiency of fixed asset use and continuing to pay attention to its financing structure to achieve a better balance between equity and debt.